Community integral education and afroepistemology in Cuyagua, Venezuela - Preciado, Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The academic motivation was to approach the construction of intersubjectivities with the cimarrones of the Network of Afro-Venezuelan Organizations, from now on ROA, based on the educational experience of the Center for Community Integral Education (CEICO) who lived in the town of Cuyagua, Costa de Oro municipality of the Aragua state in the Bolivarian Republic of Venezuela. This educational experience, seen from the qualitative orientation, served as the basis to approach a theoretical-methodological reflection in relation to the presence of Afroepistemology and Afro-Epistemetodics-a category constructed by the Afro-Venezuelan professor Jesús "Chucho" García and understood as decolonial epistemology from the perspective of Modernity/Coloniality/Decoloniality-, in addition, the historical processes linked in the struggles for education in Afro-descendant communities of the country from the perspective of the teacher Luis Bigott. Likewise, the field work through the research method as a qualitative case study close to collaborative or cooperative research, allowed to relate the emerging categories of community integral education, village teachers, pedagogy of orality, epistemic racism and pedagogy of the cimarronaje, making visible the contributions of the afrodescendants, which allowed to conclude that it is necessary to build in the country a critical and political education, linked to the needs and contexts of the populations to which it is directed.